PENGARUH MINAT BELI MASYARAKAT TERHADAP DISKON SHOPEE, KUALITAS PRODUK DAN HARGA BAGI PENGGUNA SHOPEE (Study Kasus Bagi Pengguna Shopee di Sragen) - Anisa Wahyuni; Trio Handoko; Zandra Dwanita Widodo (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
ABSTRACT The purpose of the study is to find out: (1) The effect of Shope Discounts on buying interest in Sragen City, (2) The Effect of Product Quality on buying interest at Shopee, (3) The Effect of Price on buying interest, (4) The Effect of Discounts, Product quality and prices on buying interest at Shopee. This study is a quantative study with data obtained by as many as 100 respondents from the questionnaire. The conclusions of this study are: the results of the t test (partial) show that discounts and product quality have a significant effect on buying interest while price does not have a significant effect on buying interest. The results of the f test (simultaneously) obtained the result that discounts, product quality and price have a significant effect on buying interest.